ITSBAT NIKAH DAN AKIBAT HUKUMNYA (STUDI PENELITIAN DI KOTA LHOKSEUMAWE) - Assy'ra Assy'ra; Faisal Faisal; Fauzah Nur Aksa; Dara Quthni Effida (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
A marriage that is legal according to the law if the marriage is carried out according to each religion and belief and is recorded in accordance with the prevailing laws and regulations and is proven by a marriage certificate. However, some husband and wife only perform marriages that are legal according to religion and are not yet legally valid or carry out an underhand marriage so that it cannot be proven by a marriage certificate, so the couple can apply for Itsbat Nikah to the Syar'iyah Court by fulfilling predetermined conditions. This study aims to determine and understand the implementation of Itsbat Nikah in Lhokseumawe City, the legal consequences of unregistered marriages and recorded marriages. This study uses an empirical or juridical sociological method (sociological legal research) which is descriptive in the form of written or spoken words from people who are used as sources of information. The Itsbat Nikah was held in Lhokseumawe City by involving the APIK Legal Aid Institute which was energized with the government and the Syar'iyah Court in the Mobile Marriage program. The legal consequence of registering Marriage is to obtain legal certainty for married couples and children born in marriage. Itsbat Nikah can make it easier for the community to apply for a legal marriage but under the responsibility it becomes a legal marriage according to positive law and obtains a marriage book. The Lhokseumawe Government needs to socialize to the public about the importance of marriage registration, so that the community becomes more aware of the legal consequences and legal strength of marriage which is recorded in accordance with statutory regulations. Keywords: Itsbat Marriage, Legal Consequences.